ZAMZAM MART MINI MARKET BUSINESS STRATEGIES WITH CUSTOMER SURVEY AND BMC ANALYSIS - Ahmad, Zahid; Sutopo, Sutopo; Solehudin, Tohir (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
A mini market is a small store that sells various goods and food, similar to a supermarket but on a smaller scale. The presence of Zamzam Mart as a mini market run by selfemployed entrepreneurs in the Ciampea Udik region of Bogor is crucial and provides convenience for rural residents who are not accustomed to online shopping. However, the competition with franchise businesses is intense. The research aims to develop strategies to enhance Zamzam Mart's competitiveness through customer surveys. The research method involves creating a survey questionnaire with 7 questions rated on a 5-point scale, conducting surveys and data analysis, with the respondents being local consumers. The Business Model Canvas (BMC) is then analyzed. The response rate was 71% (71 out of100 questionnaires). The respondents included children (7%), adolescents (34%), young adults (14%), male adults (11%), and female adults (34%), with the highest frequency of visits being twice a week (48.3%). The survey results revealed that 47.8% of respondents rated the product prices as